IMPLIKASI KEBIJAKAN PENYERTAAN MODAL DAERAH PADA PIHAK KETIGA TERHADAP ASPEK-ASPEK PERUSAHAAN (Studi Kasusu Pada PT. Anindya) - , Edy Junaidi, Drs. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In view to boost the growth of its economy, to increase regional revenues, and to open up job opportunities, Yogyakarta Special Province has initiated cooperation with a third party. This policy is urgent in regard to the present problems in Yogyakarta, such as the lack of capital and ineffective bureaucracy for managing profit-oriented organization. It is highly expected, therefore, that the cooperation with a third party will become the best solution for the current problems. The research aims to study the policy performance and the factors affecting its implementation, as well as the implication toward the corporate aspects. It applies evaluation method in order to know the policy performance, and a case study approach in order to address the policy implication in question. It collects data by means of documentation, interview, and observation techniques, and subsequently analyses them in a qualitative method. It measures the policy performance using policy effect indicators, which consist of access, scope, frequency, and number of cooperation being established